The impact of oocyte meiotic spindle and automated zona pellucida score and sperm chromatin packaging on fertilization and pregnancy for assisted reproduction techniques - Raubenheimer, Kara (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.